ANALISIS PENGARUH FINANCIAL LEVERAGE TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN PERBANKAN - Arinda Herliana; Febiola Khoirunnisa; Wulan Alawiyah; Nasyiatu Niswah; Hilya Nur Syahidah (Determinasi: Jurnal Penelitian Ekonomi Manajemen dan Akuntansi, 2024)
Company value is an important element of a company to build a good image in society, of course there are many influencing factors, one of which is financial leverage. The purpose of this research is to prove whether or not there is a relationship and influence between financial leverage (independent variable) and company value (dependent variable) on banking companies, taking data from the Indonesia Stock Exchange (BEI) in 2022. The data taken in the form of financial reports from 20 banking companies including: PT Bank Central Asia Tbk, PT Bank Rakyat Indonesia Tbk, PT Bank Negara Indonesia Tbk, PT Bank Mandiri Tbk, PT Bank Syariah Indonesia Tbk, PT Bank Tabungan Negara Tbk, PT Bank KB Bukopin Tbk , PT Bank Raya Indonesia Tbk, PT Bank Pembangunan Daerah Jawa Timur Tbk, PT Bank BTPN Syariah Tbk, PT Bank Jago Tbk, PT Bank Pembangunan Daerah Jawa Barat, PT Bank Neo Commerce tbk, PT Bank MNC Internasional Tbk, PT Bank CIMB Niaga Tbk , PT Bank Aladin Syariah Tbk, PT Bank Capital Indonesia Tbk, PT Bank Danamon Tbk, PT Bank Ganesha Tbk, PT Bank Permata Tbk. This research is accompanied by data that is tested using multiple regression tests and descriptive statistical tests which prove that there is an influence of financial leverage on company value.